Perceived Challenges and Unmet Primary Care Access Needs among Bangladeshi Immigrant Women in Canada - Tanvir C. Turin; Ruksana Rashid; Mahzabin Ferdous; Nashit Chowdhury; Iffat Naeem; Nahid Rumana; Afsana Rahman; Nafiza Rahman; Mohammad Lasker (SAGE Publishing, 2020)
Introduction: Understanding barriers in primary health care access faced by Canadian immigrants, especially among women, is important for developing mitigation strategies. The aim of this study was to gain an in-depth understanding of perceived challenges and unmet primary health care access needs of Bangladeshi immigrant women in Canada. Methods: In this qualitative study, we conducted 7 focus groups among a sample of 42 first-generation immigrant women on their experiences in primary health care access in their preferred language, Bangla. Descriptive analysis was used for their socio-demographic characteristics and inductive thematic analysis was applied to the qualitative data. Results: The hurdles reported included long wait time at emergency service points, frustration from slow treatment process, economic losses resulting from absence at work, communication gap between physicians and immigrant patients, and transportation problem to go to the health care centers. No access to medical records for walk-in doctors, lack of urgent care, and lack of knowledge about Canadian health care systems are a few of other barriers emerged from the focus group discussions. Conclusions: The community perception about lack of primary health care resources is quite prevalent and is considered as one of the most important barriers by the grassroots community members.